1991
DOI: 10.1007/bf00319853
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion patterns in vascular dementia of Binswanger type compared with senile dementia of Alzheimer type: a SPECT study

Abstract: Cerebral perfusion patterns in 18 cases with vascular dementia of Binswanger type (VDBT) (8 moderate and 10 severe cases) were compared with 25 cases with senile dementia of Alzheimer type (SDAT) (16 moderate and 9 severe cases) and 14 controls by single photon emission computed tomography using N-isopropyl-p-123I iodoamphetamine (IMP) as a tracer. The cerebral: cerebellar IMP uptake ratio (%) (CCR) was used as a measured of relative cerebral perfusion. The CCRs were about 85-90% in all areas in controls. Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 45 publications
2
16
0
1
Order By: Relevance
“…Our SPECT study with a 3D-SSP technique demonstrated differences in rCBF between BD and AD: anterior cerebral cortices were more affected in BD, while posterior cerebral cortices were more affected in AD, which is consistent with previous results obtained by conventional ROI analysis and statistical image analysis [1][2][3][4][5]. However, the rCBF pattern of each patient is more variable, and a distinct CBF reduction in the temporoparietal and/or posterior cingulate regions, indistinguishable from the perfusion pattern of AD, was observed in some of those with BD, in particular a bilateral hemispheric reduction in those with a diffuse hypoperfusion pattern.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our SPECT study with a 3D-SSP technique demonstrated differences in rCBF between BD and AD: anterior cerebral cortices were more affected in BD, while posterior cerebral cortices were more affected in AD, which is consistent with previous results obtained by conventional ROI analysis and statistical image analysis [1][2][3][4][5]. However, the rCBF pattern of each patient is more variable, and a distinct CBF reduction in the temporoparietal and/or posterior cingulate regions, indistinguishable from the perfusion pattern of AD, was observed in some of those with BD, in particular a bilateral hemispheric reduction in those with a diffuse hypoperfusion pattern.…”
Section: Discussionsupporting
confidence: 94%
“…Functional brain imaging studies using positron emission tomography (PET) or single photon emission CT (SPECT) may be useful in the diagnosis and understanding of the pathophysiology in patients with vascular or Binswanger's dementia. Although several investigators have examined regional cerebral blood flow (rCBF) patterns in patients with BD [1][2][3], most of the previous studies were conducted by visual assessment or region of interest (ROI) analysis on brain images, which involve various problems, such as too much subjectivity, poor reproducibility, and acquisition of information only in the ROI. New image-processing and statistical programs allowing pixel-by-pixel analysis of CBF and metabolism have provided a reliable and objective evaluation of the severity, extent, and localization of regional abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Although reduced perfusion in the parietal and temporal cortices has been shown to be a characteristic initial perfusion pattern of Alzheimer's disease, perfusion reduction subsequently becomes apparent in other corti cal areas with the progress of dementia [38,43,44], The present results are for the most part consistent with these findings.…”
Section: Discussionsupporting
confidence: 82%
“…One study of PET in Binswanger's disease, a clinical variant of VaD, revealed a decrease of CBF and the cerebral metabolic rate for oxygen in the white matter and cortex [30]. Other studies with SPECT have shown that CBF was diffusely reduced [1], or that blood flow was mainly reduced in the frontal lobe [2][3][4]. Thus, no definite conclusions have been reached about the cerebral circulation and metabolism in VaD.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have found various imaging patterns related to cerebral function in VaD patients, such as a patchy decrease of blood flow [1] or reduced blood flow in the frontal lobes [2][3][4]. However, this reduced blood flow is not necessarily specific for VaD.…”
Section: Introductionmentioning
confidence: 95%